Portal vein aneurysm associated with arterioportal fistula after hepatic anterior segmentectomy: Thought-provoking complication after hepatectomy - Yusuke Kimura; Tomohide Hori; Takafumi Machimoto; Tatsuo Ito; Toshiyuki Hata; Yoshio Kadokawa; Shigeru Kato; Daiki Yasukawa; Yuki Aisu; Yuichi Takamatsu; Taku Kitano; Tsunehiro Yoshimura (Surgical Case Reports, 2018)
Abstract Background Few cases of postoperative arterioportal fistula (APF) have been documented. APF after hepatectomy is a very rare surgery-related complication. Case presentation A 62-year-old man was diagnosed with hepatocellular carcinoma in segments 5 and 8, respectively. Anterior segmentectomy was performed as a curative surgery. Each branch of the hepatic artery, portal vein, and biliary duct for the anterior segment was ligated together as the Glissonean bundle. The patient was discharged on postoperative day 14. Three months later, dynamic magnetic resonance imaging showed an arterioportal fistula and portal vein aneurysm. Surprisingly, the patient did not have subtle symptoms. Although a perfect angiographic evaluation could not be ensured, we performed angiography with subsequent interventional radiology to avoid sudden rupture. Arteriography was immediately performed to create a portogram via the APF from the stump of the anterior hepatic artery, and portography clearly revealed hepatofugal portal vein flow. Portography also showed that the stump of the anterior portal vein had developed a 40-mm-diameter portal vein aneurysm. Selective embolization of the anterior hepatic artery was accomplished in the whole length of the stump of the anterior hepatic artery, and abnormal blood flow through the APF was drastically reduced. The portal vein aneurysm disappeared, and portal flow was normalized. Dynamic computed tomography after embolization clearly demonstrated perfect interruption of the APF. The patient maintained good health thereafter. Conclusions Post-hepatectomy APFs are very rare, and some appear to be cryptogenic. Our thought-provoking case may help to provide a possible explanation of the causes of post-hepatectomy APF.